Short Hairpin RNA-mediated MDR1 Gene Silencing Increases Apoptosis of Human Ovarian Cancer Cell Line A2780/Taxol - Xu, Hui; Hong, Fan-zhen; Li, Su; Zhang, Ping; Zhu, Lin (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: Recurrent ovarian cancer is often resistant to drugs such as paclitaxel. Short hairpin RNA (shRNA) targeting MDR1, a gene involved in the process of drug resistance, may be a promising strategy to overcome drug resistance. Methods: Construction and identification of eukaryotic expression plasmid of shRNA targeting on MDR1 gene. The plasmid was transiently transfected into human ovarian cancer cell line A2780/Taxol. Apoptosis was determined by flow cytometry using annexin V-FITC/PI double labeling. Expression of MDR1 mRNA was detected by quantitative polymerase chain reaction (qPCR) and P-glycoprotein expression was detected using Western blot. Results: The IC50 of paclitaxel in MDR1 shRNA-transfected group was significantly reduced (1.986±0.153) μmol/ml as compared with that in negative control (5.246±0.107) μmol/ml and empty vector-transfected group (5.212±0.075) μmol/ml (P